Gilbert’s Plural Subject Account in Social Ontology - Khadka, Manoj Kumar (International Journal of Psychosocial Rehabilitation, 2020)
The paper critically examines Plural Subject account as posited by Gilbert. The paper explicates the necessary conditions as laid down by Gilbert in order to legitimately claim as constituting a collective action. To this end, the paper introduces the concept of social entities and goes on to construct hypothetical cases to clearly demonstrate what constitutes a Gilberts plural subject account. Further, the paper scrutinizes arguments against Gilbert’s position as leveled by other philosopher and lastly concludes that Gilbert’s ingenious insight in her plural subject account of collective action can provide a conceptual framework to understand the dynamics of social phenomenon.